Ecoturismo en Cerro de Arcos, parroquia Manú, cantón Saraguro, provincia de Loja - Silva Curipoma, Yescela Betzabeth (2023)
The main objective of this research paperwork is to create an action plan to promote ecotourism development for Cerro de Arcos. First, we diagnosed the biophysical, tourist, socioeconomic, and cultural status; second, we realized an analysis of the tourist perception of the population and third, the formulation of the tourism action plan. The data obtained indicate that Cerro de Arcos has a variety of unique ecosystem goods and services in the area that show ecotourism potential, including the presence of fauna (Blue-throated Star Hummingbird "Oreotrochilus Cyaenolemus" and Andean Condor "Vultur gryphus"), flora representative of the area, and rock formations (andesites and alternating lava). The demand profile considers the interest in experiencing a diversity of landscapes and the search for adventure and challenges, attributing activities such as hiking and photography. However, the tourist plant in the Manú parish is not extensive. The population perceives tourism as an activity that can be beneficial from a social, ecological, and economic point of view. Therefore, we established four lines of action to guarantee the conservation of the ecosystem, the use of tourism, and the direct and indirect benefits to the population.